2018
DOI: 10.1001/jamacardio.2017.5205
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Omega-3 Fatty Acid Supplement Use With Cardiovascular Disease Risks

Abstract: This meta-analysis demonstrated that omega-3 fatty acids had no significant association with fatal or nonfatal coronary heart disease or any major vascular events. It provides no support for current recommendations for the use of such supplements in people with a history of coronary heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
332
2
23

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 574 publications
(370 citation statements)
references
References 30 publications
13
332
2
23
Order By: Relevance
“…In the main results, omega-3 fatty acid supplementation had no significant association with CHD death (rate ratio [RR] 0.93; 99% CI 0.83 to 1.03), non-fatal MI (RR 0.97; 99% CI 0.87 to 1.08) or any CHD events (RR 0.96; 95% CI 0.90 to 1.01) 1. Omega-3 supplementation also had no significant association with major vascular events (RR 0.97; 95% CI, 0.93 to 1.01) overall or in any subgroups.…”
mentioning
confidence: 82%
See 3 more Smart Citations
“…In the main results, omega-3 fatty acid supplementation had no significant association with CHD death (rate ratio [RR] 0.93; 99% CI 0.83 to 1.03), non-fatal MI (RR 0.97; 99% CI 0.87 to 1.08) or any CHD events (RR 0.96; 95% CI 0.90 to 1.01) 1. Omega-3 supplementation also had no significant association with major vascular events (RR 0.97; 95% CI, 0.93 to 1.01) overall or in any subgroups.…”
mentioning
confidence: 82%
“…A meta-analysis of large randomised trials has assessed the association of omega-3 fatty acid (eicosapentaenoic acid [EPA] and docosahexanoic acid [DHA]) supplement use with the risk of fatal and non-fatal cardiovascular heart disease (CHD) and major vascular events 1. The meta-analysis (10 trials; 77,917 high-risk people) included studies that involved at least 500 participants and ran for at least 1 year (mean duration 4.4 years) 1.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A recent meta-analysis demonstrated that omega-3 fatty acids had no significant association with fatal or nonfatal coronary heart disease or any major vascular events [29]; however, there are currently no published CVD outcome trials using these agents. Both the Reduction of Cardiovascular Events with EPA-Intervention Trial (REDUCE-IT) and Outcomes Study to Assess STatin Residual Risk Reduction with EpaNova in HiGh CV Risk PatienTs with Hypertriglyceridemia (STRENGTH) are underway and will hopefully help determine this class’ position in diabetic dyslipidemia.…”
Section: Combination Therapiesmentioning
confidence: 99%